Cell‐Permeable Peptides Containing Cycloalanine Residues. Issue 41 (16th August 2016) - Wu, Hao; Mousseau, Guillaume; Mediouni, Sonia; Valente, Susana T.; Kodadek, Thomas
Abstract: We present here an efficient alternative to N‐methylation for the purpose of morphing protein‐binding peptides into more serum‐stable and cell‐permeable compounds. This involves the incorporation of a cycloalanine (CyAla) into a peptide in a way that avoids difficult coupling steps. We demonstrate the utility of this chemistry in creating a cell‐permeable derivative of a high‐affinity HIV Rev protein‐binding peptide. Abstract : Introducing sites of N‐alkylation into peptides improves serum stability and cell permeability. The most common strategy, N‐methylation, requires harsh peptide‐coupling reactions. An alternative strategy is proposed involving the efficient incorporation of cycloalanine residues into peptides. This approach was employed to create a cell‐permeable version of a HIV Rev peptide antagonist.